2021
DOI: 10.1093/geront/gnaa223
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centeredness in Older Adults With Multimorbidity: Results of an Online Expert Delphi Study

Abstract: Background and Objectives Older adults suffering from multimorbidity represent a priority target group for patient-centeredness (PC). We aimed to investigate the transferability of an existing integrated model of PC comprising 15 dimensions on the care of older adults with multimorbidity from an expert perspective. Research Design and Methods 242 experts were invited to participate in a two-round online Delphi study. In the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
2
8
0
1
Order By: Relevance
“…Considering the rather deductive approach of our study and the fact that the emerging topics could be fully assigned to our pre-defined PC dimensions, data saturation may be assumed. Of note, our study findings suggest that the perceptions of multimorbid older people correspond closely with PC’s conceptual dimensions as experts have proposed [ 41 ], and with current guidelines for the patient-centered care of elderly people with multimorbidtiy [ 19 ]. Together, these different perspectives may be integrated within a population-specific adaptation of the PC model which will serve to develop patient-centered interventions and assessment instruments for PC in this specific patient group.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Considering the rather deductive approach of our study and the fact that the emerging topics could be fully assigned to our pre-defined PC dimensions, data saturation may be assumed. Of note, our study findings suggest that the perceptions of multimorbid older people correspond closely with PC’s conceptual dimensions as experts have proposed [ 41 ], and with current guidelines for the patient-centered care of elderly people with multimorbidtiy [ 19 ]. Together, these different perspectives may be integrated within a population-specific adaptation of the PC model which will serve to develop patient-centered interventions and assessment instruments for PC in this specific patient group.…”
Section: Discussionsupporting
confidence: 77%
“…Population-specific aspects not covered by the existing model’s dimensions were assigned to the newly-proposed PC dimension ‘individual care needs related to aging and chronic disease’. This dimension was developed on the basis of an initial literature search and expert Delphi survey within our research project [ 41 ] and has now been confirmed from the patient’s perspective within the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision-making about tailoring critical care for multi-morbid individuals, especially in the very old, require consideration and weighting of patient-centred outcome measures such as quality of life vs burden of treatment [33]. Short-and long-term goals should be determined by the expectations of the individual patient, which may differ from recommendations for managing single conditions in younger people.…”
Section: Managing Multi-morbiditymentioning
confidence: 99%